Flavor volatiles evolution of Chinese horse bean-chili-paste during ripening, accessed by GC×GC-TOF/MS and GC-MS-olfactometry. Issue 1 (1st January 2020) - Lu, Yunhao; Tan, Xinyi; Lv, Yuanping; Yang, Guohua; Chi, Yuanlong; He, Qiang
ABSTRACT: The evolution of volatile compounds during the ripening of Chinese horse bean-chili-paste (CHCP) was investigated in this study. GC×GC-TOF/MS allowed an identification of 748 volatiles in three CHCP samples, respectively, ripened for 3 months (M3), 12 months (M12) and 24 months (M24), and it showed that a longer ripening resulted in a richer diversity of the volatiles. In addition, M3 contained more aldehydes and organic acids in content and M12 had more alcohols, ketones, and esters, while M24 was abundant in heterocyclics. A total of 69 among the 748 volatiles were discriminated as the key flavor compounds of CHCP by method of Fisher ratio together with odor activity value and flavor dilution, including 12 alcohols, 9 aldehydes, 4 ketones, 5 organic acids, 16 esters, 4 phenols, 6 sulfur-containing compounds, and 13 heterocyclics. Further, principal component analysis suggested that some key aldehydes contributed the flavor of M3, while some key alcohols, esters and heterocyclics existed in M12, and some key phenols and heterocyclics were in M24. Varying of the key flavor volatiles during CHCP ripening gave it different fragrance configurations. Results presented details for the volatile profiles of CHCP during the natural ripening period, beneficial to shorten fermentation time by functional microorganisms, and could enrich the desire flavors.